Comparative proteomic analysis reveals the adaptation of Herpetospermum pedunculosum to an altitudinal gradient in the Tibetan Plateau. (October 2018) - Kim, Hyok Chol; Peng, Mu; Liu, Shuo; Wang, Yaojie; Li, Zishuo; Zhao, Shidong; Li, Shuanghui; Quan, Hong; Luo, Qiuxiang; Meng, Fanjuan
Abstract: H. pedunculosum, a well-known alpine plant, is widely distributed in high-altitude regions and can survive in the extreme environment of the Tibetan Plateau (TP). In this study, we used proteomic technologies to study the tolerance mechanism of H. pedunculosum to high altitudes, namely, 2800 m, 3000 m, 3100 m and 3300 m. A total of 52 proteins were successfully identified and classified into eleven groups based on their molecular functions, i.e., cytoskeleton dynamics (3), energy (5), carbohydrate metabolism (9), photosynthesis (11), protease (2), transcription (5), stress and defense (6), molecular chaperones (3), protein synthesis (2), other materials metabolism (2) and unknown function (4). These results indicated that the chloroplast pathway as well as the production of signaling, the ROS-scavenging pathway and the Calvin cycle pathway may collectively mediate adaptation to high altitudes in H. pedunculosum . Based on these findings, we concluded that the high level of expression of some proteins, such as oxygen-evolving enhancer proteins, calreticulins, and S-adenosyl-l -homocysteine hydrolase, might confer H. pedunculosum with greater tolerance to the complex environment associated with high altitudes. In addition, we surmised that high altitudes can induce protein changes in H. pedunculosum . Highlights: H. pedunculosum, can survive in extreme environment of the Tibet Plateau. We firstly used proteomic technologies to study the tolerance mechanism of H. pedunculosum to high altitude. We surmised that high altitudes can induce protein changes of H. pedunculosum.